DIALECTIC INTERACTION OF EDUCATION AND SUBJECTIVITY AS A SUBJECT OF PHILOSOPHICAL ANALYSIS - Kamardash, N. V. (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2017)
It is necessary to have information about the internal and external determinants of educational system for the efficiency and performance its functioning. The method of system and critical analysis, the multidisciplinary approach, allowed the explication of the postmodern educational situation in the context of the problem of the essence and existence of subjectivity in the ontological conditions of globalization and the internationalization of the world process. On the basis of the analysis of the genesis of the education system, a transformation of subjectivity was revealed, interconnection of social, economic, cultural and educational factors were identified, a philosophical assessment of changes educational trends in postmodern conditions was conducted. The main attention is paid to the issue of spirituality, the relation between spiritual and social, language and practice in the structure of subjectivity and place of education in the system of socialization.